Игнаш сайкемын: роман / Р. С. Игнатьева - Игнатьева Римма Серафимовна (Удмуртия, 2020)
Экземпляры: ф.2 (2020) / Инвентарный номер: 56366 / Цена: 600.00. / Сис.шифр: К84(2Рос=Удм) / Авт.знак: И 26 / ГРНТИ: 17.82.31 / ББК: 84(2=664.1)^VLBC/M